Down-regulation of circPTTG1IP induces hepatocellular carcinoma development via miR-16-5p/RNF125/JAK1 axis. (1st September 2022) - Peng, Rui; Cao, Jun; Su, Bing-Bing; Bai, Xue-song; Jin, Xin; Wang, Ao-qing; Wang, Qian; Liu, Ren-jie; Jiang, Guo-qing; Jin, Sheng-jie; Zhang, Chi; Bai, Dou-sheng
Abstract: Circular RNAs are known to regulate the biological processes of hepatocellular carcinoma (HCC), and humans with Down syndrome are at low risk of developing solid tumors due to the amplification of several tumor suppressor genes on human chromosome 21 (HSA21). Here, we aimed to investigate the potential role of circRNAs originating from HSA21 in the progression of HCC. CircRNA-sequencing was performed to analyze differentially expressed circRNAs in 4 HCC and peritumor tissues, and circRNAs originating from HSA21 were further analyzed. Circ_0061984 (circPTTG1IP) was chosen for further study because it showed the lowest expression in HCC tissues, and qRT-PCR was used to confirm the expression of circPTTG1IP in HCC patient tissues. The biological function of circPTTG1IP was detected in HCC cells both in vivo and in vitro. Moreover, luciferase reporter assays, circRNA immunoprecipitation, and fluorescence in situ hybridization (FISH) were used to investigate the potential mechanism of circPTTG1IP. Finally, the possible mechanisms of filgotinib in circPTTG1IP-driven HCC were assessed. CircPTTG1IP expression was decreased in HCC compared to peritumoral tissues. Moreover, low circPTTG1IP expression was revealed to be associated with a poor prognosis of HCC patients. Elevation of circPTTG1IP was revealed to inhibit HCC development both in vitro and in vivo. Mechanistically, circPTTG1IP was shown to function as a competing endogenous RNA (ceRNA) of RNF125 by binding miR-16-5p to increase the level of the E3 ubiquitin ligase RNF125, which further ubiquitinated and degraded JAK1 protein. Finally, we demonstrated that administration of filgotinib, a JAK1 inhibitor, restricted HCC progression induced by low circPTTG1IP expression. Thus, we revealed that circPTTG1IP is a novel tumor suppresser circRNA in HCC and that a low circPTTG1IP level promotes HCC development via the miR-16-5p/RNF125/JAK1 axis. Patients with low circPTTG1IP may benefit from filgotinib treatment. Highlights: CircPTTG1IP from HSA21 crucially regulates HCC development via the miR-16-5p-RNF125-JAK1 signaling axis. CircPTTG1IP downregulation favors the inflammatory environment by inducing macrophage recruitment and M2 polarization. Filgotinib remodels the tumor microenvironment by inhibiting circPTTG1IP-JAK1 axis, which may benefit patient prognosis.